2015
DOI: 10.1136/gutjnl-2014-308379
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance alters hepatic ethanol metabolism: studies in mice and children with non-alcoholic fatty liver disease

Abstract: NCT01306396.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 43 publications
(48 reference statements)
2
91
0
2
Order By: Relevance
“…While short-chain fatty acids enhance intestinal absorption by activating glucagon-like peptide-2, ethanol causes triglyceride accumulation in hepatocytes via production of reactive oxygen species and initiation of liver inflammation. This might provide a second hit to the liver that had already accumulated fat [81][82][83]. Furthermore, the gut-derived bacterial products stimulate innate immune receptors, namely Toll-like receptors (TLRs), expressed on most hepatic cells, thus contributing to acute and chronic liver diseases via immune activation, i.e.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…While short-chain fatty acids enhance intestinal absorption by activating glucagon-like peptide-2, ethanol causes triglyceride accumulation in hepatocytes via production of reactive oxygen species and initiation of liver inflammation. This might provide a second hit to the liver that had already accumulated fat [81][82][83]. Furthermore, the gut-derived bacterial products stimulate innate immune receptors, namely Toll-like receptors (TLRs), expressed on most hepatic cells, thus contributing to acute and chronic liver diseases via immune activation, i.e.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Also, intragastric administration of ethanol (1 g/kg) to rats with SIBO evoked a 10-fold increase in the portal concentration of acetaldehyde, whereas portal and systemic BACs reached negligible values [70]. Another study showed similar portal venous concentrations of ethanol in obese and lean mice, suggesting intraluminal FPM of ethanol in the obese group [125]. In addition, host ADH3 present in the stomach, small bowel, and liver may play a significant role in FPM of ethanol.…”
Section: Equation (3): Calculating Circulation Alcohol Burden (Cab)mentioning
confidence: 67%
“…A plausible explanation is that chronic exposure to ethanol leads to hyperinsulinemia [125], which shifts energy supply from glucose to ketone bodies [65]. In turn, high ketone bodies alongside oxidized carbohydrates and iron overload shift ethanol metabolism from low Km ADH1 (that works in the millimolar range) to high Km alcohol-metabolizing enzymes (that work in the molar range) [65,141] such as cytochrome P450 2E1 (CYP2E1), ADH4, and ADH3 [28,30,66,69,126,142,143].…”
Section: Discussionmentioning
confidence: 99%
“…"oth studies demonstrated that the gut microbiota proile in pediatric N"FLD is diferent from lean healthy children, with more ethanol-producing bacteria, suggesting that endogenous alcohol production by intestinal microbiota may play a role in N"FLD pathogenesis. Engstler et al also showed that fasting ethanol levels were positively associated with measures of insulin resistance and signiicantly higher in children with N"FLD than in controls [60]. Interestingly, with further animal experiments, they demonstrated that increased blood ethanol levels in children with N"FLD may result from insulin-dependent impairments of alcohol dehydrogenase activity in liver tissue rather than from an increased endogenous ethanol synthesis [60].…”
Section: Nafld In Children Gut Microbiota and Nafld In Childrenmentioning
confidence: 97%
“…Engstler et al also showed that fasting ethanol levels were positively associated with measures of insulin resistance and signiicantly higher in children with N"FLD than in controls [60]. Interestingly, with further animal experiments, they demonstrated that increased blood ethanol levels in children with N"FLD may result from insulin-dependent impairments of alcohol dehydrogenase activity in liver tissue rather than from an increased endogenous ethanol synthesis [60]. Taken together, human studies demonstrated signiicant diferences in gut microbiota between normal subjects and patients with N"FLD.…”
Section: Nafld In Children Gut Microbiota and Nafld In Childrenmentioning
confidence: 99%